Evaluation of connectivity, flux pinning, and upper critical field contributions to the critical current density of bulk pure and SiC-alloyed MgB2 - Matsumoto, A.; Kumakura, H.; Kitaguchi, H.; Senkowicz, B. J.; Jewell, M. C.; Hellstrom, E. E.; Zhu, Y.; Voyles, P. M.; Larbalestier, D. C. (My University, 2006)
Measurement of critical current density Jc, normal state resistivity rho_n, and upper critical field Hc2 on pure and 10% SiC-doped MgB2 bulks show systematic enhancement of Hc2 by SiC addition and by lowering reaction temperature. Hc2 (10 K) exceeds 33 T, while the extrapolated zero temperature value exceeds 40 T. The Rowell [ Supercond. Sci. Technol. 16, R17 2003] analysis suggests that only 8%?17% of the MgB2 cross section actually carries current. Higher reaction temperature enhances the connectivity but degrades Hc2 and flux pinning, making the measured Jc a complex balance between connectivity, Hc2, and flux pinning induced by grain boundaries and precipitates.
Keywords: superconductivity; MgB2